Double phosphates NaMn₆(P₃O₁₀)(P₂O₇)₂ and KMn₆(P₃O₁₀)(P₂O₇)₂ - advanced functional materials - Nagorny, P.G.; Slobodyanik, N.S.; Ushchapivska, T.I.; Lavrik, R.V. (Functional Materials, 2018)
Complex phosphates containing two different ions have been identified in the fluxes of M₂O-P₂O₅-Mn₂O₃ systems (where M - Na, K) for the first time. Optimum conditions for the growing of single crystals of NaMn₆(P₃O₁₀)(P₂O₇)₂ and KMn₆(P₃O₁₀)(P₂O₇)₂ compounds have been selected. Complete X-ray diffraction analysis has been performed to study single crystals of synthesized phosphates MMn₆(P₃O₁₀)(P₂O₇)₂ (where M - Na, K). The structure of compounds is defined by the monoclinic crystal system (space group P2₁/m) with lattice parameters: a = 5.350 (5.358) Å, b =26.643 (26.697) Å, c = 6.566 (6.575) Å, β = 107.25⁰ (107.22⁰); Z = 2, ρ = 3.575(3.568) g/cm³, respectively. The synthesized compounds have been studied using the following techniques: DTA, IR- and EPR-spectroscopy, magnetochemistry; the dependence of dielectric constant on the temperature has been measured for the obtained phosphates. Slight antiferromagnetic interaction has been detected in octahedron chains [MnO6]. Based on the findings from conducted research, a set of physicochemical properties has been proposed for the synthesized compounds, which can be utilized in the development of these functional materials.